Relato sobre anomalia no comportamento de uma grande barragem mista de terra e concreto com-pactado com rolos em operação – o caso da Barragem Castanhão - Baima, Sandra Keila de Oliveira (2017)
This paper describes, in detail, the occurrence of an anomaly in the behavior of a large earth- concrete dam, which has been in operation for eleven years in the Northeast region of Brazil. In mid-2014, with the drought-related lowering of the reservoir level, a vertical crack was observed in the concrete of the junction core wall of block number 13 in the spillway. The delay in taking actions to fix the anomaly has allowed the information about the issue to be known by the general public, through press reports, causing great fear to the population of Jaguaribe river valley downstream areas. The institution that owned the dam, DNOCS, hired a specialized technical consulting firm to prepare a diagnostic report and to propose measures to remedy the anomaly. The results of the studies conducted by this consulting firm and the proposed corrective measures are presented in the final section.